Pendampingan Retorika Dakwah Dalam Meningkatkan Efektivitas Public Speaking Guru Smks Al-Hidayah Depok - Fadhila, Nurul; Nala Azkia Azahra (Rayah Al-Islam, 2025)
Currently, public speaking skills are very important for teachers in delivering teaching materials and in effectively promoting student enrollment. However, many teachers lack the confidence needed for this. This community service activity applies the concepts of Dakwah Rhetoric from Aristotle and Lasswell, where rhetoric is seen as the art of speaking with both informative and persuasive abilities. The goal is to help teachers become more confident in delivering engaging and effective lessons. The method used in this service activity is Participatory Action Research (PAR), an approach aimed at addressing problems and meeting the practical needs of the community while also producing knowledge. This method involves collaboration between researchers, participants, and students to solve the challenges faced by teachers in improving their public speaking effectiveness.